Studying Vulnerable Populations Through an Epigenetics Lens: Proceed with Caution - Saulnier, Katie; Berner, Alison; Liosi, Stamatina; Earp, Brian; Berrios, Courtney; Dyke, Stephanie; Dupras, Charles; Joly, Yann (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Epigenetics – the study of mechanisms that influence and modify gene expression – is providing unique insights into how an individual’s social and physical environment impact the body at a molecular level, particularly in populations that experience stigmatization and trauma. Researchers are employing epigenetic studies to illuminate how epigenetic modifications lead to imbalances in health outcomes for vulnerable populations. However, the investigation of factors that render a population epigenetically vulnerable present particular ethical and methodological challenges. Here we are concerned with demonstrating how, in targeting certain populations for epigenetic research, this research may be pathologizing socio-cultural and medical practices in those populations in a way that increases their vulnerability. Using a case study approach, this article examines three vulnerable populations currently of interest to epigenetic researchers – Indigenous, autistic, and transgender populations – in order to highlight some of the challenges of conducting non-stigmatizing research in epigenetics.